Rapid Pseudocapacitive Sodium‐Ion Response Induced by 2D Ultrathin Tin Monoxide Nanoarrays. (20th February 2017) - Chen, Minghua; Chao, Dongliang; Liu, Jilei; Yan, Jiaxu; Zhang, Bowei; Huang, Yizhong; Lin, Jianyi; Shen, Ze Xiang
Abstract : Nanostructured tin‐based anodes are promising for both lithium and sodium ion batteries (LIBs and SIBs), but their performances are limited by the rate capability and long‐term cycling stability. Here, ultrathin SnO nanoflakes arrays are in situ grown on highly conductive graphene foam/carbon nanotubes substrate, forming a unique, flexible, and binder‐free 3D hybrid structure electrode. This electrode exhibits an excellent Na + storage capacity of 580 mAh g −1 at 0.1 A g −1, and to the best of our knowledge, has the longest‐reported high‐rate cycling (1000 cycles at 1 A g −1 ) among tin‐based SIB anodes. Compared with its LIB performance, the enhanced pseudocapacitive contribution in SIB is proved to be the origin of fast kinetics and long durability of the electrode. Moreover, Raman peaks from the full sodiation product Na15 Sn4 at 75 and 105 cm −1 are successfully detected and also proved by density functional theory calculations, which could be a promising clue for structure evolution analysis of other tin‐based electrodes. Abstract : Flexible, binder‐free electrode composed of 2D ultrathin (≈2.5 nm) SnO nanoflake arrays on graphene foam/carbon nanotubes foam is fabricated. Density functional theory calculation, quantitative capacitive analysis, and ex situ Raman and high‐resolution transmission electron microscopy verify the role of pseudocapacitive contribution to high‐rate Na + storage and long‐term cycle life of sodium ion battery.